Influence of Micropollutants on E. coli and Total Coliforms Removals in Flat PBR - Pompei, Caroline Moço Erba [UNESP]; Ruas, Graziele [UNESP]; Bolzani, Hugo Renan [UNESP]; Fernandes, Luiza Maria [UNESP]; da Silva, Gustavo Henrique Ribeiro [UNESP] (Springer Nature, 2025)
The microalgae-based systems is an interesting solution to minimize the problems among the pollution of water with micropollutants and E. coli and total coliforms because of the inefficient sewage treatment. The purpose of this study was to be a preliminary investigation if the presence of selected micropollutants could interfere in the removal process of E. coli and total coliforms by a pilot-scale flat panel photobioreactor (50 L) operated outdoors with real sewage under tropical climate. The system was operated in batch mode (7 days duration each), and the samples were made daily into two different operational conditions: with and without micropollutants (3 batches each). E. coli removal efficiency by flat panel did not change in the presence of micropollutants (3.66 log-Re 99.97%) or no (4.27 log-Re 99.3%), while the presence of micropollutants seems to influence to worst (3.79 log-Re and 99.9%; 1.77 log-Re and 98.2%) in the total coliforms removal by the system (p = 0.0086). The total conforms seems to be more resistant to environmental variations, and more susceptible to micropollutants presence than E. coli. The system is efficient to remove the coliforms bacteria group from sanitary sewage, however the presence of micropollutants seems to negatively influence the total coliforms removal by the system, requiring further investigation.